Antimicrobial potential, phytochemical profile, cytotoxic and genotoxic screening of sedum praealtum a. DC. (balsam) - Gomes Boriollo, Marcelo Fabiano; Marques, Milene Bueno; Da Silva, Thaísla Andrielle; Da Silva, Jeferson Júnior; Dias, Reigson Alves; Silva Filho, Thyago Henrique Neves; Ribeiro Melo, Isadora Letícia; Dos Santos Dias, Carlos Tadeu; De Carvalho Bernardo, Wagner Luís [UNESP]; De Mello Silva Oliveira, Nelma; Peters, Vera Maria; Höfling, José Francisco; et al. (Springer Nature, 2020)
Background: Sedum praealtum has been used for a long time in traditional medicine as an analgesic and antiinflammatory agent. Its beneficial effects have been known since ancient times, when Latinos used it to treat sore and swollen eyes. This research evaluated the antimicrobial potential, the cytotoxic and genotoxic effects, and some chromatographic profiles of the hydroethanolic extract of leaves, stems and roots of S. praealtum. Methods: The antimicrobial activities were carried out by broth microdilution and agar diffusion. In vitro cytotoxicity was evaluated by cell cultures of Aedes albopictus and the selectivity index (SI) was estimated: SI=CI50/MIC. Genotoxic and systemic toxic effects of S. praealtum leaves were analyzed by micronucleus assay in mice bone marrow. Chromatographic profiles and mass spectra were investigated by GC-MS. Results: Gram-positive (B. subtilis, B. cereus, M. luteus, E. faecalis and S. aureus) and gram-negative (E. coli, E. aerogenes, S. marcescens, P. aeruginosa, P. mirabilis and S. typhimurium) bacteria exhibited MICs ranging from 12.5–50 and 0–50 mg/ ml, respectively. Sedum praealtum showed no efficacy against M. tuberculosis and M. bovis. Cytotoxicity (CI50) of S. praealtum was 4.22 and 5.96 mg/ml for leaves and stems, respectively, while its roots showed no cytotoxicity. Micronucleated polychromatic erythrocytes (MNPCEs) analyzes showed no differences between treatment doses (0.5–2 g/kg) and negative control (NaCl), but the PCE/NCE ratio (polychromatic erythrocyte/normochromatic erythrocyte) showed significant differences. Phytochemical screening identified thirteen compounds in the leaves, stems and roots of S. praealtum potentially associated with their biological activities. Conclusions: This research comprises a first scientific study on genotoxicity, cytotoxicity and antimicrobial effects of S. praealtum (Balsam), and it provides an initial theoretical foundation for its comprehensive use. Results showed antibacterial action of S. praealtum against gram-positive bacteria and some gram-negative species (depending on the plant anatomical part), but ineffective antimycobacterial action. However, S. praealtum leaves and stems display potential cytotoxicity, contributing to the SI < 1 values. In addition, S. praealtum leaves exhibit no clastogenic and/or aneugenic effects, but it has systemic toxicity dose-independent.
Keywords: Antimicrobial susceptibility; Cytotoxicity; Genotoxicity; Phytochemical screening; Sedum praealtum a. DC